2022
DOI: 10.1111/jth.15725
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism after COVID‐19 vaccination

Abstract: Background COVID‐19 vaccinations in the United States are effective in preventing illness and hospitalization yet concern over post‐vaccination venous thromboembolism (VTE) risk has led to vaccine hesitancy. Methods The aim of this study was to compare VTE rates before and after COVID‐19 vaccination. COVID‐19 vaccinated patients ≥18 years between November 1, 2020 through November 1, 2021 were analyzed using electronic medical records across the Mayo Clinic enterprise. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…These findings are consistent with other population based post-market studies that observed no increased risk of developing thromboembolic events following receipt of the BNT162b2 vaccine [5] , [11] , [12] , [13] , [14] , [15] . Conversely, a SCCS study in the United Kingdom (UK) found an increased risk of CVT and arterial thrombosis 15–21 days after a first dose of the BNT162b2 vaccine [6] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with other population based post-market studies that observed no increased risk of developing thromboembolic events following receipt of the BNT162b2 vaccine [5] , [11] , [12] , [13] , [14] , [15] . Conversely, a SCCS study in the United Kingdom (UK) found an increased risk of CVT and arterial thrombosis 15–21 days after a first dose of the BNT162b2 vaccine [6] .…”
Section: Discussionsupporting
confidence: 91%
“…New Zealand's COVID-19 Vaccine and Immunisation programme began vaccinations in February 2021 and almost exclusively uses the BNT162b2 vaccine [9] . Although the Pfizer-BioNTech phase III clinical trials [10] and subsequent international observational studies [5] , [11] , [12] , [13] , [14] , [15] have not found an association between the two, thrombotic events have been reported following the BNT162b2 vaccine through the New Zealand spontaneous reporting (passive surveillance) system [16] and internationally [17] , [18] . Moreover, a self-controlled case series (SCCS) study in England reported an increased risk of cerebral venous thrombosis (CVT) and arterial thrombosis during the 15 to 21 days after the first dose of the BNT162b2 vaccine [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Immune activation through viral infections or vaccinations can lead to inflammation, and inflammation is linked to an increased risk of VTE (see sections ‘Infection’ and ‘Inflammation’). If VTE is triggered by mRNA-based vaccines, the relative and absolute risks are minuscule, because studies with millions of people who received an mRNA-based COVID-19 vaccine have not detected consistent associations with VITT 54 , 56 .…”
Section: Acute Triggering Risk Factorsmentioning
confidence: 99%
“…Another issue is the potential for COVID vaccines to influence the risk of VTE. In this regard, most recent studies have reported no influence of vaccines on the incidence of VTE (30,31), except perhaps for the ChAdOx1 vaccine(32) but overall it seems that vaccines are safe in this regard. This information was not available in the studies included in this review.…”
Section: Accepted Manuscriptmentioning
confidence: 98%